(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The Construction division is one of the important economic and it is the important motivating force in Indian economy. it travels from a number of problems that affect time, cost and quality performances. Best management of construction projects is depends on three major factors which are time, cost and quality. Time delay and Cost overruns has been a big matter in many Indian construction projects. The successful completion of construction projects within the given time has become the most valuable and challenging task. The good execution of construction site and keeping them in estimated cost and prescribed schedules depend on a method that requires sound engineering judgment. Delays are incidents that impact a project’s speed and postpone project activities. The actual date of completion is invariably different from the expected date. Construction delay is a major problem facing by the construction industry. In most construction projects, there are delays and their impact level varies from project to project ranging from a few days to years. Therefore the purpose of dissertation is to find the causes of delay and cost overrun. To find out the most significant factors affecting Time and project Cost overruns and suggest guideline for minimum of effects of delays for construction projects.